English as a Lingua Franca: Concepts and Differences with World Englishes - Adinda Zahra Hidayat; Hilmah Rahmatul Amalia; Aidil Syah Putra (International Journal of English Education and Linguistics (IJoEEL), 2026)
English has become a global means of communication used by speakers from diverse linguistic and cultural backgrounds. This condition challenges the traditional view of English that prioritizes native-speaker norms and standard varieties. Two influential frameworks that address this global use of English are English as a Lingua Franca (ELF) and World Englishes (WE). However, the conceptual distinction between these two perspectives is often unclear, particularly in educational contexts. This study aims to explore students’ understanding of English as a Lingua Franca and its differences from World Englishes within the framework of Teaching English as an International Language (TEIL). The research employed a qualitative descriptive design involving 15 undergraduate students of an English Education program at Universitas Muhammadiyah Tangerang. Data were collected through open-ended questionnaire responses and analyzed using thematic qualitative analysis. The findings reveal that most participants perceive ELF as a functional tool for communication that emphasizes intelligibility and mutual understanding rather than native-speaker accuracy. Meanwhile, World Englishes is generally understood as recognizing the existence of multiple English varieties shaped by local and cultural contexts. Although many participants were able to distinguish between ELF and WE, some conceptual overlap was evident. Overall, the study suggests the importance of explicitly integrating ELF and WE concepts into TEIL to promote a more inclusive and realistic understanding of English as a global language.